Non-native English Students’ Linguistic and Cultural Challenges in Australia - Tananuraksakul, Noparat (Journal of International Students, 2012)
This paper looks into the effect of use of international English on non-native students’ dignity in Australian academic and social contexts. The study was undertaken through in-depth interviews with 28 participants from 13 countries. The results partly revealed that there was neither speech convergence nor culture convergence between non-native and native speakers. When native speakers linguistically converged towards non-native speakers, it appeared to backfire as mocking behavior. There was an expectation that host tutors, lecturers and classmates would adjust their speech to a level accommodating non-native speakers, but they did not. Failure to effectively converge linguistically and culturally led to failure in intergroup communication. The failure concomitantly affected participants’ self-worth, motivation and identity in a way that diminished their dignity and motivation, impinging on their identity.